Risk Factors of Stunting in Toddlers 24-59 Months in Rembang Regency, Indonesia - Galuh Ramaningrum; Hema Dewi Anggraheny; Aisyah Lahdji (South East Asia Nursing Research, 2022)
Rembang Regency is an area in Central Java with a fairly high stunting rate, in 2017 it reached 32.36%. The Sedan Health Center is located in Rembang Regency with a stunting prevalence in 2019 of 7.16%. This is still a serious problem in the region. Risk factors for stunting include child and maternal risk factors. Child risk factors include food intake, birth weight, gender, history of chronic disease, history of breastfeeding, complementary foods, socio-economic, environmental sanitation, and immunization status. The purpose of this study was to determine what factors influence stunting in the working area of the Sedan Health Center. This research used observational analytic research with a case-control design and has been matched based on age. The research was carried out from January-February 2021. The number of samples was 45 cases (stunted toddlers) and 45 controls (non-stunted toddlers). Data were collected by measuring the height of children under five and interviewing with a questionnaire. Data analysis used the chi-square test and logistic regression test. Variables of energy intake (p=0.000), protein, history of exclusive breastfeeding (p=0.000), history of complementary feeding (p=0.000), number of family members (p=0.001), and family sanitation (p=0.000) had significant outcome was associated with the incidence of stunting. The most influential factor is the history of complementary foods. Stunting cases occur in children with low energy and protein intake. A varied food intake especially with a high-calorie and high-protein composition can prevent children from stunting.